Aikido the basics : techniques, principles, concept - Roedel, Bodo 1971-; Gaertel, Nadja; Werner, Susen (Maidenhead Meyer & Meyer Sport, 2011)
This title presents a superbly illustrated and easy-to-follow overview of the basic principles, concepts, and techniques of Aikido. Aikido is the Japanese martial art developed by Morihei Ueshiba in the early 20th century as a synthesis of other martial arts and a philosophy of peace, the goal of which was to create an art that could be used by practitioners to defend themselves while also protecting the aggressor from serious injury. Filled with full-colour illustrations and written by an enormously experienced and successful Aikido instructor, this volume presents readers with a comprehensive overview of the basic principles, concepts, and techniques of this specialized martial art - from proper foot and hand movements to the 'roles' of both the defender and attacker.
What is Aikido -- Foot movements -- Hand movements -- Working up techniques -- Details of the Aikido techniques -- Aikido is based on principles -- Learning Aikido -- Learning the role of Uke-ukemi -- Further information.
Includes bibliographical references (pages 332-333), glossary and index.
Keywords: Aikido